Lessons Learned from Long-Term Assessment of Rotavirus Vaccination in a High-Income Country: The Case of the Rotavirus Vaccine Belgium Impact Study (RotaBIS) - Standaert, Baudouin (Infect Dis Ther, 2020)
INTRODUCTION: The rotavirus (RV) vaccine Belgium Impact Study (RotaBIS) evaluated the vaccine effect on RV-related hospital care in children up to 5 years old over a period of 13 years. Different forces were identified that influence the reduction in hospital care. Our analysis aims to report on the current RotaBIS dataset and explore through model simulation whether, how, and when the results could have been improved. METHODS: As performed in previous assessments, this analysis evaluated RV-related events per year, per age group, RV nosocomial infections, hospitalization duration, and herd effect. It subsequently identified results that were surprising or unexpected. To know whether those data could have been improved through specific interventions, we developed a model with the forces acting on the disease transmission and the vaccine effect on RV-related hospital care. Scenario analysis of the forces should explain the current findings and identify ways to optimize the results. RESULTS: The RotaBIS data show that annual RV-related hospital cases (n = 1345 pre-vaccination) dropped by 70% (95% confidence interval [CI] 66–74%) by year 5 (n = 395) after vaccine introduction, and by 84% (95% CI 79–89%) by year 10 (n = 217). The herd effect during the first year was limited to 14% extra gain. During the last 5 years, small disease increases were seen biennially. The simulation model indicates that higher vaccine coverage of the major transmitters during the peak season of the first year of vaccination could have reduced RV-related hospital care by nearly 90% at 5 and 10 years after vaccine introduction owing to a higher herd effect. The smaller peaks observed in recent years would have been dramatically reduced. CONCLUSION: The current RotaBIS data show a maintained reduction, around 76%, in RV hospitalization cases. Simulations show that these results could have been improved to an important extent with a more optimal initiation of the vaccination program. TRIAL REGISTRATION: ClinicalTrials.gov identifier, NCT01563146 and NCT01563159. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40121-020-00345-y) contains supplementary material, which is available to authorized users.